KAJIAN PEMANFAATAN POTENSI SUMBER DAYA AIR TERPADU ( STUDI KASUS MATA AIR INGAS (COKRO), KEC. COKRO TULUNG KABUPATEN KLATEN – JAWA TENGAH) - Sriyana Sriyana (Diponegoro University, 2011)
Potential exploitation of Ingas (Cokro) water resource is currently less than optimal, there are still manywasted water flows and there is still no coordination in planning. The objective of this research is to reviewwater resource potential integratedly, by measuring the spring discharge in real terms, analyzing the utilizationof water source and water balance. The method used in this thesis is by measuring the discharge using currentmeter, analyzing water requirements for plants using Penman method, and analyzing data with the help ofMicrosoft Exel. It is resulted that the total potential of Ingas (Cokro) water resource is 1297 l/dt, utilized fordrinking water (PDAM Surakarta) at 400 l/dt, drinking water for Cokro Village at 4 l/dt, and the remainder isused for irrigation and moving a turbine with 50 Watt electric power. Water demand for irrigation is 995 l/dt,fullfilled from Ingas (Cokro) source discharge at 593 l/dt plus surface water discharge as a result frommeasurment of pulsur river (Plosowareng weir) at 696 l/dt, from the total water resource potential of 1289 l/dt.Water balance of Ingas (Cokro) water resource has already balanced or optimal, while residual discharge of294 l/dt is obtained at measurement point (Plosowareng weir)